Environmental exposure to organophosphate esters and suspected non-alcoholic fatty liver disease among US adults: A mixture analysis - Haisheng Chai; Weiye Hu; Yaoyao Dai; Xiaohan Zhu; Ping'an Qian; Junfeng Zhu; Junfeng Zhu (Frontiers Media S.A., 2022)
ObjectivesNon-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide. We evaluated NAFLD using the US FLI to determine whether there is an association between urinary organophosphorus (OPE) levels and the "prevalence" of NAFLD in US individuals.MethodsThe current study included 1,102 people aged 20 years and older with information from the 2011-2014 U.S. National Health and Nutrition Examination Survey. NAFLD was assessed using the U.S. FLI. Individual OPE metabolites and OPE combinations were linked to NAFLD using logistic regression and weighted quantile sum (WQS) regression. All analyzes were carried out separately on males and females. The possible impacts of age, serum total testosterone (TT), and menopausal state, as well as the importance of the interaction term with exposure, were investigated using stratified analysis.ResultsBis (2-chloroethyl) phosphate and bis (1,3-dichloro-2-propyl) phosphate were associated with NAFLD in all males after adjusting for covariates (P < 0.05). A combination of OPEs (OPE index) was positively linked with NAFLD in the WQS analysis of all males (odds ratio for OPE index: 1.52; 95% CI: 1.06, 2.19). Stratified analyzes for males revealed that considerable connections were largely confined to individuals over 60 years old or with low total testosterone. In women, the connection was limited and inconsistent, except for the OPE index, which was positively linked with NAFLD in post-menopausal women.ConclusionsIn this study, environmental exposure to OPE was linked to an elevated risk of NAFLD in males, particularly those over 60 years old or with low TT levels. Aside from the continuous positive connection of a combination of OPEs with NAFLD risk in post-menopausal women, these correlations were weaker in women. However, these findings should be taken with caution and verified in future investigations by collecting numerous urine samples in advance to strengthen OPE exposure estimates.